Feasibility of cultivation of Spinibarbus sinensis with coconut oil and its effect on disease resistance (nonspecific immunity, antioxidation and mTOR and NF-kB signaling pathways). Issue 93 (October 2019) - Wu, Pan; Yang, Weiguang; Dong, Yuying; Wang, Yanling; Zhang, Ying; Zou, Xuejun; Ge, Hui; Hu, Dongxue; Cui, Yubo; Chen, Zhaobo
Abstract: Application of traditional bait in aquaculture caused environment pollution and disease frequent occurrence. Residual coconut could be re-utilized to culture Spinibarbus sinensis as dietary supplement. Therefore, a novel integrated system of the improvement of yield, antioxidant and nonspecific immunity of Spinibarbus sinensis by dietary residual coconut was proposed and investigated. Spinibarbus sinensis could grow well in all supplement residual coconut groups. Survival rate, yield, whole fish body composition under 15–45% groups were increased compared with control group (CK). Bioactive substances (polyphenols and vitamin) in residual coconut enhanced AKP, ACP, phagocytic, SOD, CAT activities through up-regulating AKP, ACP, SOD, CAT genes expression levels. Theoretical analysis showed bioactive substances regulated these genes expressions and enzyme activities as stimulus signal, component, active center. Moreover, residual coconut improved mTOR and NF-kB signaling pathway. Furthermore, residual coconut inhibited Aeromonas hydrophila that increased resistance to diseases. This technology completed the solid waste recovery and the Spinibarbus sinensis culture simultaneously. Highlights: To culturing spinibarbus sinensis bydietary residual coconut. The residualcoconut improved yield and survival rate. The residual coconut enhancednonspecific immunity, antioxidant, disease resistance capacities. The residualcoconut improved mTOR, NF-kB signaling ransduction pathway. New strategypromoted the solid waste recovery, Spinibarbus sinensis growth performance.